Prehabilitation before cancer surgery in the UK National Health Service: what services exist, and how do they address health inequalities? - Hilary Stewart; Xiubin Zhang; Yasemin Hirst; Laura Wareing; Lisa Ashmore; Christopher Gaffney; Charlotte Hadley; Ces Kulikowski; Jo Rycroft-Malone; Clifford Shelton; Andrew Smith (PLoS ONE, 2026)
Objectives To identify and map prehabilitation services for patients preparing for cancer surgery in the UK National Health Service (NHS) and understand how issues of accessibility and inequality are being addressed. Design A survey based on the Template for Intervention Description and Replication and criteria for high-quality, equitable prehabilitation developed as part of our broader study. Setting National Health Service organisations in the UK. Participants Representatives of prehabilitation services, who were mainly healthcare professionals. To be eligible for inclusion, services had to be part of the funded usual care pathway for patients in the NHS trust or health board and offered, referred to, or signposted by the NHS cancer care team. Outcomes The primary outcome was the availability of a prehabilitation service to patients who were preparing for cancer surgery at a given NHS organisation. Where prehabilitation services existed, we collected data on service characteristics, the size and workload of the service, screening and individualised assessment for prehabilitation, interventions, addressing inequalities, and evaluation of the service. Results Of 152 NHS organisations which provided cancer surgery services, we received a response from 112 (74%). Of these, 73 (65%) stated that they had an eligible prehabilitation service, and 39 (35%) stated that they did not. We received detailed survey responses from 51/73 prehabilitation services (70%). These demonstrated variability across all survey domains. Most services involved physiotherapists (43; 84%) and dietitians (37; 73%), with a variety of other professions represented. Twenty-four prehabilitation services (47%) reported that they tailor initial assessments to account for patient characteristics, and most services reported that they take steps to address inequities of access, the most common being support for people who have barriers to accessing the internet (46; 90%). Only 19 prehabilitation services (37%) were in receipt of permanent funding. Conclusions Prehabilitation provision for people preparing for cancer surgery varies widely across the UK, and this creates inequities in services. Nevertheless, prehabilitation services appear to be aware of the risk of unequal access, and are taking steps to address this. There is an opportunity to address inequalities as prehabilitation services are commissioned, developed and implemented.